ANALYSIS OF THE INFLUENCE OF SELF-EFFICACY AND SOCIAL SUPPORT ON STUDENT ACADEMIC ACHIEVEMENT (CASE STUDY: STIE SUTAATMADJA STUDENT): Array - Lingga Larasati Ilmira; Diaz Salsafa (JABI (Journal of Accounting and Business Issues), 2025)
The advancement of higher education is closely tied to the quality of human resources it produces, with both internal and external factors significantly influencing students’ academic success. This study aims to evaluate the extent to which self-efficacy and social support affect academic achievement among university students. Self-efficacy refers to a student’s belief in their capability to successfully carry out academic tasks, while social support encompasses emotional and instrumental assistance from the surrounding environment, including family, peers, and lecturers. This research investigates the impact of these two variables both individually (partially) and collectively (simultaneously) in enhancing academic performance. The study was conducted using a sample of 52 students from STIE Sutaatmadja, specifically from the Accounting and Management departments. The findings are expected to provide valuable insights into the psychological and social factors that shape the learning process and to serve as a foundation for developing more effective support strategies in higher education institutions.